Anomalous structural dynamics in liquid Al80Cu20: An ab initio molecular dynamics study. (15th September 2015) - Wang, W.Y.; Han, J.J.; Fang, H.Z.; Wang, J.; Liang, Y.F.; Shang, S.L.; Wang, Y.; Liu, X.J.; Kecskes, L.J.; Mathaudhu, S.N.; Hui, X.; Liu, Z.K.
Graphical abstract: Abstract: In this work, the structural dynamics of liquid Al80 Cu20 is systematically investigated in terms of the evolution of its atomic structure, diffusivity, viscosity and fragility through ab initio molecular dynamics simulations. In addition to using pair correlation functions and coordination numbers, the various local ordered clusters are characterized comprehensively by Honeycutt-Anderson bond pairs and Voronoi polyhedra. Compared to the self diffusivity of pure liquid Cu, the tracer diffusion coefficients of Cu in liquid Al80 Cu20 are increased, in agreement with the results measured by quasielastic neutron-scattering (QENS). Although the interdiffusion coefficients predicted by Darken's equation match well to those obtained from the viscosity measurements via the Stokes-Einstein relation, they are smaller than those measured by QENS or X-ray radiography, indicative of an anomalous nature of the structural dynamics, dominated by the local ordered clusters in liquid Al80 Cu20 . Furthermore, Vogel–Fulcher–Tammann fitting results indicate that the liquid Al80 Cu20 can be classified into a strong liquid. The deformation electron density shows that the intrinsic tetrahedral-type bonds in FCC Al and Cu are transformed into an amorphous type in liquid Al80 Cu20 . The present work provides insights into the understanding of structural dynamics and the kinetic properties of such metallic melts.